The effect of substrate diameter and incline on locomotion in an arboreal frog - Herrel, Anthony (2013)
Frogs are characterized by a unique morphology associated with their saltatory lifestyle. Yet, arboreal species show morphological specializations relative to other ecological specialists allowing them to hold on to narrow substrates. However, almost nothing is known about the effects of substrate characteristics on locomotion in frogs. Here, we quantified the 3D kinematics of forelimb movement for frogs moving across branches of different diameters (1 and 40 mm) and two different inclines (horizontal and 45 deg uphill). Our results show that grip types differ while moving across substrates of different diameters and inclines. The kinematics of the wrist, elbow and shoulder as well as the body position relative to the substrate also showed significant effects of individual, diameter and incline. Kinematic differences involved duration, velocity of movement and angular excursions. Differences were most pronounced for the proximal joints of the forelimb and effects for substrate diameter were greater than for incline. Interestingly, the effects of diameter and incline on both grip type and kinematics are similar to what has been observed for lizards and primates, suggesting that the mechanics of narrow substrate locomotion drive the kinematics of movement independent of morphology and phylogeny.